Legal Models of Providing Payment Initiation Services - Zbigniew DŁUGOSZ (Communications of International Proceedings, 2021)
The dynamic growth of e-commerce has necessitated the development of efficient and user-friendly ways to settle online transactions. One of the new services enabling such settlements is the payment initiation service regulated in EU law by Directive 2015/2366 on payment services (PSD2). However, since this service and the related regulations have been in place for a relatively very short time now, some of the rules of its operation still raise significant concerns. The aim of the paper is to identify possible legal models for the provision of the payment initiation service. In particular, it analyses possible options of the contractual relationship between the payment initiation service provider, the payer and the payee. This analysis will answer the question to whom the payment initiation service is provided, as well as how the design of these relationships may affect its practical application, particularly within e-commerce.
Keywords: Payment Services; Payment Initiation Service; PSD2; Open Banking; E-commerce